Between Memory and Power : The Syrian space under the late Umayyads and early Abbasids (c. 72-193/692-809) - Borrut, Antoine (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2023)
Between Memory and Power intends to demonstrate that a robust culture of historical writing existed in 2nd/8th century Syria, and to offer new methodological approaches to access this now lost history, torn between memory and oblivion. By studying the making of Umayyad heroes or Abbasid origins-myths, this book aims to reveal the successive meanings granted to Syrian history, and to identify the various layers of historical writing and rewriting during the first centuries of Islam. Taken together, these elements make possible a history of meanings of the very space of Syria, articulated around power and its expression, which grants a clear coherence to the period, extending well beyond the dynastic caesura of 132/750.